The China economy yearbook. - Liu, Guoguang, 1923- (Chinese Academy of Social Sciences yearbooks. Economy ;, 2008)
The first English edition of The China Economy Yearbook contains articles investigating the Chinese economy in the past year from various perspectives, ranging from decision-making at the macro level to key industries at the medium level, including real estate, foreign trade, the automotive industry, financing, and investment.